An evolutionary system for recognition and tracking of synoptic-scale storm systems - Parikh, Jo Ann; Daponte, John S; Vitale, Joseph N; Tselioudis, George (Pattern Recognition Letters, 1999)
An evolutionary system was developed for generation of complete tracks of northern midlatitude synoptic-scale storm systems based on optical flow and cloud motion analyses of global satellite-based datasets produced by the International Satellite Cloud Climatology Project (ISCCP). The tracking results were compared with low sea level pressure anomaly (SLPA) tracks obtained from the NASA Goddard Institute for Space Studies (GISS). The SLPA tracks were produced at GISS by analysis of meteorological, ground-based National Center for Environmental Prediction (NCEP) datasets. Results from the evolutionary system were also compared with results from using (a) the k-nearest neighbor rule (k-NN) and (b) self-organizing maps (SOM) to determine correspondences between consecutive locations within a track. The consistency of our evolutionary storm tracking results with the behavior of the low sea level pressure anomaly tracks, the ability of our evolutionary system to generate and evaluate complete tracks, and the close comparison between the results obtained by the evolutionary, k-NN, and SOM analyses of the ISCCP-derived datasets at tracking steps in which proximity or optical flow information sufficed to determine movement, demonstrate the applicability and the potential of evolutionary systems for tracking midlatitude storm systems through low-resolution ISCCP cloud product datasets.
Keywords: Computational methods; Data structures; Image analysis; Nearest neighbor analysis; Optical flows; Pattern recognition systems; Self-organizing maps; Storms; Synoptic-scale storm systems; Weather forecasting; cloud; dept.csc; pattern recognition; satellite imagery; storm track; synoptic meteorology